Potential of Social Capital and Community Participation in Village Development (Universitas Negeri Semarang, 2019)
This study aims to evaluate the development program of Tlogoadi Sleman village which is related to social capital and community participation. Social capital as the potential of natural resources and human resources, while community participation is the activity of individuals or groups in village development programs. The research subjects consisted of 12 hamlet heads in Tlogoadi village, and data collection using questionnaire methods and in-depth interviews. Data analysis was descriptive quantitative and qualitative. The results showed that the average social capital of 80% supports the development activities of the village of Tlogoadi and 85% involves community participation. Evaluation based on the utilization of resource potential carried out by Tlogoadi village shows that 75% of the potential of natural resources and human resources are used in rural development which can reduce poverty. Future studies need to be tested on community members from each hamlet to find out the consistency of the results.